PENGEMBANGAN MODUL ANGIOSPERMAE BERBASIS KETERAMPILAN PROSES UNTUK MELATIH KEMANDIRIAN BELAJAR SISWA KELAS X SMA - PURNAMASARI, MAYA (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2014)
Curriculum 2013 suggests was desired that learning process is learning emphasizes the personal experience through process skills (observation, listening, viewing, reading, listening), asking, conclusioning, and communicate to training the self learning. Based on the pra-experiment that already done at Mojokerto 3 Senior High School knowing that the students is not training about skill process and self learning. Among 73,5% responsdens says that they really feel so hard to understand a material about plant world specially the Angiosperm. Therefore, the researchers developed teaching materials in the form of modules with skills-based material angiosperms process with the goal to produce a decent module used and describe the feasibility of modules based on the theoretical aspects of result validation module and empirical aspects of student activity observed when using the module and student responsse results. This research includes research development with reference to the 4-D model of development which is divided into four stages, namely: the definition phase (define), stage design (design), stage of development (develop), and the deployment phase (dessiminate). Deployment phase is not implemented. The instrument used the sheet module validation, observation of student activity sheets, and sheet student questionnaire responsses. The instrument used the sheet module validation, observation of student activity sheets, and sheet student questionnaire responsses. The instrument used the sheet module validation, observation of student activity sheets, and sheet student questionnaire responsses. Quantitative data were analyzed descriptively. The results of this research is a skill-based modules angiosperms based on the viability of process theoretically and empirically. Feasibility module theoretically obtain validation of the results of the interpretation of the value of 3.70 is very feasible. Feasibility module empirically based observations of student activity gets a percentage of 86.4% with very good interpretation, while the responsse from the students get a percentage of 93.95% with a very decent interpretation. The conclusion is the Angiosperm module based on skill process can train the self learning on students. Keywords: Angiosperm Module, Skill Process, Self-Learning.